The CRETA Project: Embracing a New Religious Paradigm. An Italian Feminist Participatory Research Study in the Light of Modern Matriarchal Studies - Piccoli, Alessandra; Fleckinger, Andrea; Chiavassa, Angela (Fieldwork in Religion, 2022)
This article gives an account of a two-year project named CRETA (participatory construction of egalitarian societies) carried out by a group of 20 people in northern Italy. The initiative has tried to find concrete paths to establish an egalitarian society by building a new religious paradigm inspired by Modern Matriarchal Studies. After intensive training sessions, the participants began to develop concrete steps to get closer to the goal of creating an egalitarian community. The core aspects of matriarchal spirituality chosen by the participants which inspired the whole project are gender equality, immanent divinity and a cyclical worldview. The article presents the main results of the feminist participatory research that accompanied the community project. The pursuit of the participants to establish new, egalitarian religious practices is discussed and the challenges and achievements are reflected.